The future of coworking spaces in Cebu a scenario-driven technology foresight - Jain, Charisse Ann D. (University of the Philippines Diliman, 2022)
The Covid-19 pandemic, the digital transformation of the modern world and the proliferation of the gig economy have brought significant changes in the business landscape, prompting to the rise in popularity of coworking spaces. To investigate the future of the coworking space industry, the study focused on Metro Cebu, identified as one of the top earners among independent contractors.